La irrelevancia del consentimiento informado en los litigios de responsabilidad médica. Un análisis de la experiencia civil y estatal en Colombia - Cely León, Jorge Enrique (2022)
ABSTRACTThis article provides a general review of medical liability in the Colombian experience, specifically based on the jurisprudence of the Civil Chamber of the Supreme Court of Justice and the Third Section of the Council of State. All the above, intend to raise a critique of the irrelevance of the figure of informed consent in the liability trial, a matter that reconsiders some of the basic assumptions for the emergence of an indemnity obligation in the field of medical liability. KEYWORDS: Medical liability, Civil Law, Administrative Law, Informed Consent. RESUMENEste artículo ofrece una revisión general de la responsabilidad médica en la experiencia colombiana, específicamente, a partir de la jurisprudencia de la Corte Suprema de Justicia y del Consejo de Estado. Todo lo anterior, para plantear una crítica a la irrelevancia de la figura del consentimiento informado en el juicio de responsabilidad, cuestión que replantea algunos de los supuestos básicos para el surgimiento de una obligación indemnizatoria en materia de responsabilidad médica. CÓDIGO JEL: H75, I18.